PERCEPTION TOWARDS VIRTUAL ONBOARDING AFTER CAMPUS PLACEMENT (International Journal of Food and Nutritional Sciences, 2022)
Virtual onboarding has almost become a necessity in current ongoing global pandemic. Management institutions attracts students joining with one of their objectives of getting a job through the campus placement process provided by the institutions. Across the globe management institutions experienced complete virtual placement process been held by most of the organizations due to ongoing Covid-19 pandemic. Technology has been an enabler towards ensuring trouble free virtual placement process in which corporate, institute and students from across India connected with each other and completed the process in virtual form. After the virtual teaching learning experience and campus placement process the most critical and final stage, students must still go through is their virtual onboarding with the company after completing of their two-year post-graduation in management. Meaning of Onboarding refers to induction of an individual as a new employee into the new work environment of an organization to become part and existing team where he or she will be joining (Adler and Castro 2019). Virtual onboarding poses many challenges for all key stakeholders i.e., the company, new hire, and the institution involved in the campus placement process.